Islam dan Demokrasi dalam Perspektif Fatima Mernissi - Fajarwati, Ana Bilqis (Program Studi Studi Agama-Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2011)
In most of her works, Mernissi tried to portray that religious teachings could be easily manipulated. Mernissi, therefore also believe that the oppression of women is a kind of tradition that made-up and not from Islamic teachings. So she was very brave and not afraid to unload a tradition that is considered as sacred by the community over the years. She also draws attention to the concept of hijab. Hijab is very dominant theme in the Mernissi’s intellectual career. It is because that matter affect herself and her families, and of course other Muslim families. Hijab, which is an instrument restriction, segregation and exclusion of women from public space, according to Mernissi is the dominant form of religious understanding (dominated by men). By doing interpretations of al-Qur'an and the Hadith, historical research and sociological analysis, Mernissi strives to dismantle this understanding, and then provide an alternative interpretation. Therefore, this article attempts to describe Fatima Mernissi’s view on Islam and democracy, compared with other perspectives of Moslem intellectual. This article does not only elucidate the connection between Islam and democracy but also scrutinize the essential meaning of democracy and how historical Islam practically deals with the issue of democracy. There are three models of connectivity between Islam and democracy. First, symbiotic-mutualistic: there is no separation between Islam and democracy. Second, there is no connection between both. Third, connection with notes and critics